2016
DOI: 10.1590/1983-084x/15_176
|View full text |Cite
|
Sign up to set email alerts
|

O Processo de trabalho dos enfermeiros da atenção primária e a Política Nacional de Plantas Medicinais/Fitoterápicos

Abstract: RESUMO:O estudo objetivou conhecer o processo de trabalho dos enfermeiros da atenção primária em relação à Política Nacional de Plantas Medicinais e Fitoterápicos. O referencial foi baseado em Guareschi e Kleinman. A abordagem foi qualitativa, descritiva. Fizeram parte dos estudos enfermeiros de 21 municípios da região Sul do estado do Rio Grande do Sul. Os dados foram coletados por questionário autoadministrado, no período de junho a agosto de 2013. A análise seguiu a proposta operativa de Minayo, emergindo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 4 publications
1
4
0
13
Order By: Relevance
“…A study carried out in Southern Brazil confirms these results, indicating that of the 40 plants indicated by the subjects of this study, 17 are used or indicated by primary care nurses. 2 Studies from the Northeast also indicate the use of plants similar to those found by this study. 12,13 Nonetheless, some plants used therapeutically by the subjects of this study are based solely on popular knowledge, as there is no scientific proof of their actions and effects.…”
Section: Had a Little Stomachache I Was Taking Omeprazole And Dipysupporting
confidence: 86%
See 2 more Smart Citations
“…A study carried out in Southern Brazil confirms these results, indicating that of the 40 plants indicated by the subjects of this study, 17 are used or indicated by primary care nurses. 2 Studies from the Northeast also indicate the use of plants similar to those found by this study. 12,13 Nonetheless, some plants used therapeutically by the subjects of this study are based solely on popular knowledge, as there is no scientific proof of their actions and effects.…”
Section: Had a Little Stomachache I Was Taking Omeprazole And Dipysupporting
confidence: 86%
“…22 In a study conducted in the South, with nurses from the FHS, it was found lack of knowledge regarding the National Policy of Medicinal Plants and Phytotherapics and little participation in training activities on the subject. 2 This fact indicates the need for continuing education processes and motivation of these professionals for the correct and safe use of integrative practices, especially concerning medicinal plants and herbal medicine that are the most used by the Brazilian population.…”
Section: Had a Little Stomachache I Was Taking Omeprazole And Dipymentioning
confidence: 99%
See 1 more Smart Citation
“…Contudo estudos evidenciaram que, apesar do desenvolvimento, ampliação e difusão do tema no país, há uma precariedade no que tange ao processo de formação dos profissionais da saúde, visto que estudantes podem concluir a sua graduação sem ter contato com o estudo das plantas medicinais (14,15) . Desse modo, em relação a orientações quanto às plantas medicinais, estudos demonstram um déficit no conhecimento, evidenciado no processo formativo dos profissionais da saúde, constituindo um obstáculo para a atuação e implementação de atividades relacionadas ao uso de plantas medicinais nos serviços de saúde (8,16) .…”
Section: Introductionunclassified
“…O desconhecimento sobre a PNPIC (12) é observado em estudos nacionais (8,12,16,17) e alguns autores (18,19) atribuem tal fato à pouca divulgação, ao ceticismo e ao fato de os profissionais ainda estarem propensos ao modelo biomédico, além do fato de esse assunto não ser abordado na academia, fomentando ainda mais esses padrões. Ao ignorar essa temática durante a formação do profissional da saúde, a implementação dessa política torna-se mais dificultosa, pois conhecer as PICS possibilitaria respaldar o uso dessas terapias e garantir segurança para o usuário e o prescritor (17,19) .…”
Section: Introductionunclassified